MODERN METHODS IN FOREIGN LANGUAGE TEACHING METHODOLOGY. ("Conference on Universal Science Research 2023", 2023)
Learning and teaching foreign languages has become the need of the hour in our country-Uzbekistan as well as in all developed and developing countries. It would not be wrong to say that the conditions created today for young people and all our compatriots for learning foreign languages are proving their positive results. Among the reforms carried out in our country, attention is being paid to foreign languages, especially English. Not only in the case of foreign languages, but also in all areas of the world of science, serious changes and updates are being carried out on all fronts. it is about use.